2018
DOI: 10.1039/c8ta07861k
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the thermoelectric power factor of Sr0.9Nd0.1TiO3 through control of the nanostructure and microstructure

Abstract: Doping with zirconia controls A site cation ordering in Sr0.9Nd0.1TiO3 and significantly enhances the thermoelectric power factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 66 publications
6
39
0
Order By: Relevance
“…Similarly, we also demonstrated that adjusting the amount of additives can control the distribution of A site ions, and inhibit nanoinclusion formation, thereby signicantly increasing the thermoelectric power factor. 29 In this work, we seek to understand how the addition of graphene derivatives into the bulk matrix improves the properties of the material. The clear advantages of these additives are their scale and two-dimensional geometry (with lateral dimensions much larger than thickness) which may introduce interesting effects on each of the thermoelectric variables.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, we also demonstrated that adjusting the amount of additives can control the distribution of A site ions, and inhibit nanoinclusion formation, thereby signicantly increasing the thermoelectric power factor. 29 In this work, we seek to understand how the addition of graphene derivatives into the bulk matrix improves the properties of the material. The clear advantages of these additives are their scale and two-dimensional geometry (with lateral dimensions much larger than thickness) which may introduce interesting effects on each of the thermoelectric variables.…”
Section: Introductionmentioning
confidence: 99%
“…The net benefit of the graphite processing environment becomes apparent in the data for maximum power factor (electronic supplementary material, figure S7) increasing, for example, to approximately 1.80 × 10 −3 W m −1 K −2 at 350 K for x = 0.10. This type of increase is reflected in all other samples sintered under graphite, with an average σ S 2 value of 1.0 × 10 −3 W m −1 K −2 for compositions with x ≤ 0.40 from 475 to 975 K. This improvement was due to the significant enhancement of σ dominating the reduction of |S| with carbon burial sintering, together giving some of the highest values reported for SrTiO 3 -based thermoelectrics [16].
Figure 9.Temperature dependencies of ( a ) electrical conductivity, ( b ) Seebeck coefficient, ( c ) total thermal conductivity and ( d ) ZT values of the samples prepared in graphite.
…”
Section: Resultsmentioning
confidence: 85%
“…A similar approach was followed by Kovalevsky et al [15], but their work was limited to a low concentration of vacancies. While there have been numerous studies of La doping of SrTiO 3 [16], there have been comparatively few of other lanthanides. One exception is that of Pr substitution by Dehkordi et al [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lowest Seebeck coefficient and highest power factor(~ 1000 µV/m. K 2 ) were obtained for the same composition leading to a ZT of 0.37 at 1015 K [32]. To tune the thermal conductivity, substituting Ca and Ba at the A site has resulted in lowering the same [33,34].…”
Section: Srtiomentioning
confidence: 92%